2009 IEEE/IFIP International Conference on Dependable Systems &Amp; Networks 2009
DOI: 10.1109/dsn.2009.5270291
|View full text |Cite
|
Sign up to set email alerts
|

An end-to-end approach for the automatic derivation of application-aware error detectors

Abstract: Critical Variable Recomputation (CVR) based error detection provides high coverage for data critical to an application while reducing the performance overhead associated with detecting benign errors. However, when implemented exclusively in software, the performance penalty associated with CVR based detection is unsuitably high. This paper addresses this limitation by providing a hybrid hardware/software tool chain which allows for the design of efficient error detectors while minimizing additional hardware. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…In this case, the path tracking alone incurs a time overhead of up to 400%, while the overhead due to variable checking is up to 80% [15]. Complete hardware implementations of path tracking and expression checking are proposed in [15] and [14]. In fact, between the extreme solutions of implementing all error detection in software, on the one side, and performing it in hardware, on the other side, there is a wide range of possible alternatives characterized by the particular implementation decision taken for each process in the application.…”
Section: Preliminaries 21 Error Detection Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the path tracking alone incurs a time overhead of up to 400%, while the overhead due to variable checking is up to 80% [15]. Complete hardware implementations of path tracking and expression checking are proposed in [15] and [14]. In fact, between the extreme solutions of implementing all error detection in software, on the one side, and performing it in hardware, on the other side, there is a wide range of possible alternatives characterized by the particular implementation decision taken for each process in the application.…”
Section: Preliminaries 21 Error Detection Techniquementioning
confidence: 99%
“…As a result, customized solutions are created, tuned to better suit each application's needs. As shown in [15] and [14] the main idea of this application-aware technique is to identify, based on specific metrics [16], critical variables in a program. A critical variable is defined as "a program variable that exhibits high sensitivity to random data errors in the application" [15].…”
Section: Preliminaries 21 Error Detection Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, even if implementable, perfect detectors typically come with high resource and timing overheads. In recent work [12,18] it has been shown that the time needed for high-coverage fault detection may become much longer than the execution time of the task itself (e.g. the timing overhead could be 400% using techniques proposed in [12]).…”
Section: Introductionmentioning
confidence: 99%
“…In recent work [12,18] it has been shown that the time needed for high-coverage fault detection may become much longer than the execution time of the task itself (e.g. the timing overhead could be 400% using techniques proposed in [12]). Hence, approaches under this assumption are very pessimistic, as the most expensive fault detector is selected for every task.…”
Section: Introductionmentioning
confidence: 99%